2008
DOI: 10.1037/a0013719
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy in the veterans health administration: Missed opportunities?

Abstract: Informed by data on the dose-response effect, the authors assessed use of psychotherapy in the Veterans Health Administration (VA). The authors identified 410,923 patients with newly diagnosed depression, anxiety, or posttraumatic stress disorder using VA databases (October 2003 through September 2004). Psychotherapy encounters were identified by Current Procedural Terminology codes for the 12 months following patients’ initial diagnosis. Psychotherapy was examined for session exposure received within the 12-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
69
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 37 publications
5
69
4
Order By: Relevance
“…9 In a related study using VA databases, 22% of VA patients with a newly diagnosed condition of depression, anxiety, or posttraumatic stress disorder (PTSD) received some form of psychotherapy during the year following their initial diagnosis. 6 Further, only 8% of patients received 4 or more sessions, 4% received 8 or more sessions, and the average delay from diagnosis to first psychotherapy session was 57 days. Although distance to a VA facility was found to be a predictor of psychotherapy exposure, this study did not examine differences in psychotherapy use according to rural or urban status.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…9 In a related study using VA databases, 22% of VA patients with a newly diagnosed condition of depression, anxiety, or posttraumatic stress disorder (PTSD) received some form of psychotherapy during the year following their initial diagnosis. 6 Further, only 8% of patients received 4 or more sessions, 4% received 8 or more sessions, and the average delay from diagnosis to first psychotherapy session was 57 days. Although distance to a VA facility was found to be a predictor of psychotherapy exposure, this study did not examine differences in psychotherapy use according to rural or urban status.…”
mentioning
confidence: 99%
“…4 Distance to a provider is a significant barrier for care, especially for older adults, 5 and recent evidence suggested that distance to a VA facility is significantly related to fewer psychotherapy services for veterans. 6 Travel time and distance are also significant predictors for receiving minimally adequate care, 6,7 which places patients at greater risk for poorer depression outcomes 8 and in some cases increased mortality. 9 In a related study using VA databases, 22% of VA patients with a newly diagnosed condition of depression, anxiety, or posttraumatic stress disorder (PTSD) received some form of psychotherapy during the year following their initial diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing from Andersen's Behavioral Model [47] and previous research, we hypothesized that predisposing factors (younger age, female sex, being married or cohabitating, minority status) [52], enabling factors (residing in a rural area) [49,53], and need factors (having PTSD, desiring help for an emotional problem) [6,10,48,[54][55][56] would collectively be related to greater willingness to use e-mental health. To accomplish these goals, we surveyed a diverse sample of OIF/OEF Veterans and National Guard members in Hawaii.…”
Section: Study Aims and Hypothesesmentioning
confidence: 99%
“…"Predisposing factors" are those that exist prior to or independent of the onset of illness, such as being female, being married [48][49][50], having a higher education level [51], and having ethno-racial minority status [52]. A second determinant of use, according to the model, is "enabling factors," those contextual factors that influence access to care, such as the travel distance to obtain services [49,53]. Third, "need factors" include the presence of mental disorders or poor mental health quality of life [6,10,48,[54][55][56].…”
Section: Theoretical Approach Used In Present Studymentioning
confidence: 99%